Hyperglycemia in Hospitalized Patients Receiving Parental Nutrition Is Associated with Increased Morbidity and Mortality: A Review - Puja Rajender Kumar; Pam Crotty; Maitreyi Raman (Gastroenterology Research and Practice)
Parenteral Nutrition (PN) is a valuable life saving intervention which can improve the nutritional status of hospitalized malnourished patients. PN is associated with complications including the development of hyperglycemia. This paper aims to provide a descriptive systematic review regarding the effects of PN-induced hyperglycemia in hospitalized patients, either in the intensive care unit or ward, while formulating and complementing existing guidelines on the administration of PN and glucose monitoring in hospitalized patients. Medline and Pubmed were searched for relevant articles describing complications arising from the development of hyperglycemia in patients receiving PN; four relevant studies were identified in the search. These articles had different glycemic targets and patient populations, and their protocols varied with regards to glycemic control. However, there was consistency regarding the association between hyperglycemia and mortality in patients receiving PN. These studies highlight the need for guidelines regarding monitoring and initiation of therapy in hyperglycemic patients. Unfortunately, all the currently available studies are retrospective in design; a large, prospective, randomized controlled trial regarding glycemic control in patients receiving PN is required for the development of standardized protocols.